Chemical composition, in vitro digestibility and gas production of Brachiaria managed under different forage allowances - Ribeiro, Andressa F. [UNESP]; Messana, Juliana D. [UNESP]; Dian, Paulo H. M.; Reis, Ricardo A. [UNESP]; Ruggieri, Ana C. [UNESP]; Malheiros, Euclides B. [UNESP]; Berchielli, Telma T. [UNESP] (Pagepress Publ, 2014)
The objective of this study was to evaluate the chemical composition, in vitro digestibility, gas production and fermentation kinetics of three Brachiaria cultivars: Brachiaria brizantha cv. Marandu, Brachiaria brizantha cv. Xaraes, and hybrid Brachiaria cv. Mulato, subjected to different levels of forage allowance (4, 7, 10 and 13% of the animal body weight), under rotational grazing cycles. Cultivar Xaraes presented higher contents of neutral detergent fibre, neutral detergent fibre corrected for ash and protein, acid detergent fibre and lignin, and lower production of gases in 96 h in the component leaf blade. There was a decrease of non-fibrous carbohydrates and fraction B-2 and an increase in the fraction C of the carbohydrates in the components stem and leaf blade over the grazing cycles in all the cultivars. Cultivar Marandu presented higher digestibility values (in vitro organic matter digestibility and in vitro dry matter digestibility) in the components stem and leaf blade. Cultivar Mulato demanded a shorter time of colonisation, according to the calculations of fermentation kinetics. Regardless of the level of forage allowance and of the grazing cycles, the three Brachiaria cultivars were characterised by great fermentation quality due to the relations of the gas production potential and the gas production after 48 and 96 h.
Keywords: Acid detergent fibre; Fermentation; Neutral detergent fibre; Tropical forages